The Transformation of Arabic Language Learning in the Digital Era: A Case Study of the Implementation of Responsive Curriculum in Indonesian Private Universities - Avika Afdiana Khumaedi; Ali Burhan (PT. Anagata Sembagi Education, 2025)
This study examines curriculum innovation in Arabic language learning in private Islamic universities in Indonesia in response to the challenges of globalization, technological advancements, and changing job market needs. With a qualitative case study approach, this study shows that the integration of digital platforms, communicative teaching methods, and international collaboration can improve student learning outcomes and engagement. Institutions that apply blended learning, flipped classrooms, and industry-based Arabic courses show higher levels of adaptability and relevance. However, obstacles such as inequality of access to technology, lack of qualified lecturers, and low student motivation remain major challenges. This study contributes to the development of the field of study by presenting strategies for reforming the Arabic language curriculum based on national standards (KKNI) and international standards (ACTFL). The findings also recommend the need for further empirical evaluation and expanded cooperation with global institutions to ensure the quality and competitiveness of Arabic language learning in the long term.